Effective Use and Cost-Evaluation of Erythrocyte Suspension in Surgical Branches of Tertiary Hospital - Defne Ay Tuncel; Ayşe Yiğit Sönmez (Galenos Publishing House, 2024)
Blood has been accepted as the basic symbol of life from the past to the present. Transfusion is the transfer of blood and blood components to a patient due to various health problems. The present study aimed to evaluate the effective use and cost of erythrocyte suspension in surgical branches in a tertiary hospital. In this study, the use and cost-effective evaluation of erythrocyte suspension, a blood component, after surgical intervention in brain and nerve diseases surgery, orthopedics and traumatology, general surgery, gynecology and obstetrics, and organ transplantation clinics between 01/01/2023 and 31/12/2023 were retrospectively evaluated. Because blood products are provided as voluntary donations, their appropriate use will help reduce hospital and patient costs. We believe that strict compliance with national and international standards and guidelines, quality management, and good clinical practices, as well as ensuring continuity of training on these issues, will enable more efficient product acquisition and decrease blood component disposal in all blood services units.